SOMA 2016 : proceedings of the 20th Symposium on Mediterranean Archaeology - Oniz, Hakan,; Fazlullin, Sergei, (Access archaeology., 2022)
'SOMA 2016' focused on the archaeology of the Northern Black Sea; while rich in archaeological sites, the region is also subject to active industrial development. In addition to archaeological finds in various parts of the Mediterranean, papers focus on new ideas for the conservation and management of sites of historical and cultural heritage.